Vocabulary networks workshop 2: Activating words in a network - Paul Meara; Imma Miralpeix (Vocabulary Learning and Instruction, 2022)
Workshop 2 explores some larger vocabulary networks than those presented in Workshop 1 (1,000 words instead of 100), and introduces some additional ways of activating words in a network (e.g., by using new parameters in our models). The simulations will show that raising a network’s activation level may not be as easy as we would have expected, and that different kinds of events may cause either temporary or permanent changes in the networks. Findings will be discussed in relation to the previous literature on passive and active vocabularies. Several implications for vocabulary learning and teaching will also be considered.